Thermal power plant simulation and control - Flynn, Damian; Alessandri, A. (Institution of Electrical Engineers, 2003)
An exploration of how advances in computing technology and current areas of research can be combined to extend the capabilities and economics of modern power plants.
Title from title screen.
Keywords: Electric power-plants -- Management.; Electric power systems -- Computer simulation.; Power-plants -- Management.; Electric power systems -- Control.; elektronické knihy; electronic books